Білім берудегі инновациялық үрдіс: теория мен тəжірибе - Кушмурзина, Д.Х. (My University, 2016)
This article shows an analysis of the effectiveness of use of innovation technologies in the process of teaching and learning in the training of future teachers at the university and describes its implementation in the educational process. There are also examples of the effective methods and forms of the learning organization, which are used in the teaching of the methodological disciplines.
Keywords: innovative technology; qualification; group work.; dialogic educating; critical thinking; information technology